A Narrative Exploration of Adulthood Through the Experiences of Youths Enrolled as Adult Learners: Disrupting and Redefining What it Means to be an Adult - C. Amelia Davis (Adult Education Research Conference, 2013)
The purpose of this research was to explore the lived experience of adult basic education students, ages 18 to 25, and their construction and performance of adulthood. Findings did not support theories of development based on age-graded normative markers, indicating that traditional development theories should not be packaged as a normative path to understanding.